COMPARATIVE ANALYSIS OF USABILITY LEARNING MANAGEMENT SYSTEM IN POLITEKNIK LAMANDAU - Faizal Widya Nugraha; Hamid Muhammad Jumasa (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2020)
Learning Management System (LMS) is a tool that functions to help online class management, and has become a necessity in the learning process of higher education. Politeknik Lamandau especially in the field of Computer Engineering Technology as a developing tertiary institution has used several LMS including, Edmodo, Schoology, and Google Classroom. In its application, not all users understand the operation well due to usability issues such as complicated appearance, functions menu layout that is not user friendly, speed processing issue, the difficulty of memorizing menu functions, errors in operation that will affect user satisfaction. In this study uses the method a system usability scale test was conducted to measure the usability of the system with five components, like satisfaction, errors, efficiency, learnability, and memorability. The purpose of this study is to determine the LMS usability evaluation based on user responses. The results of the study carried out is term of usability, LMS Edmodo is categorized as acceptable with score 70 while Google Classroom and Schoology are categorized almost acceptable with score 67,6 and 64,4